A method for measuring dielectric constant of glass microspheres
By preparing the polyurethane and glass microbead composite and measuring its dielectric constant, the problem of difficulty in measuring the dielectric constant of glass microbeads in the prior art is solved, and accurate measurement of the dielectric constant and high data consistency are achieved.
Patent Information
- Application Number
- CN202210679968.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-06-15
AI Technical Summary
The prior art is difficult to measure the dielectric constant of glass beads, especially when the glass beads are present in powder state.
By preparing the polyurethane and glass microbead composite, the dielectric constant of the composite was measured, and the dielectric constant of the polyurethane without glass microbeads was calculated.
Accurate measurement of the dielectric constant of glass microbeads is achieved. The actual measured dielectric constant is very similar to the data obtained under the average field, and the lower the dielectric constant of the material itself, the closer the data is.
Smart Images

Figure FDA0003695986280000011 
Figure FDA0003695986280000012 
Figure FDA0003695986280000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass microspheres, and in particular relates to a method for measuring the dielectric constant of glass microspheres. Background Art
[0002] Hollow glass microspheres are a new type of material with wide applications and excellent performance developed in recent years. The main component of this product is borosilicate. The hollow spheres have a particle size of 10-250μm, a wall thickness of 1-2μm, and a bulk density of 0.1-0.25g / cm3. In recent years, the production of hollow glass microspheres has gradually achieved scale. There are more than a dozen manufacturers of glass microspheres in China. Many large foreign companies such as AGSCO, Mo-Sci, and 3M in the United States are engaged in the production and sales of hollow glass microspheres. The brands include: 3M, Armex, Black Beauty, Starblast, etc. These hollow glass microspheres have excellent performance. Taking 3MTM hollow glass microspheres as an example, this product has a high chemical stability and strength / density ratio and low thermal conductivity. The latest product can withstand a pressure of up to 200MPa and can be used in extrusion, injection molding and other processes. As a plastic additive, it is easy to disperse, improve melt flow, improve product dimensional stability, and reduce product weight. It is widely used in paints, coatings, building materials, injection molding and extrusion products, thermosetting plastics, spraying and lay-up molding and other fields.
[0003] Hollow glass microspheres have a lower dielectric constant due to their unique hollow structure, so hollow glass microspheres are added to high molecular organic materials such as polyurethane and epoxy resin to make the composite materials containing glass microspheres obtain better dielectric properties. However, under normal conditions, glass microspheres exist in a powder state, and their dielectric constant representing dielectric properties is relatively difficult to measure. In this context, this application proposes a method for measuring the dielectric constant of glass microspheres to solve the above problem. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a method for measuring the dielectric constant of glass beads. By preparing a composite of polyurethane and glass beads, the dielectric constant of the composite and the dielectric constant of polyurethane without glass beads are measured, and finally the dielectric constant of the glass beads is obtained.
[0005] The technical solution adopted by the present invention is as follows: A method for measuring the dielectric constant of glass microspheres, comprising the following steps:
[0006] Step 1: preparing a polyurethane solid uniformly mixed with glass microspheres, and preparing a polyurethane matrix without glass microspheres and three groups of polyurethane matrices with different glass microsphere mass fractions;
[0007] Step 2: Grind the polyurethane substrates obtained in step 1 into square sheets with a diameter of 1 cm and a thickness of 0.5-1 mm, and the thickness of the sheets is required to be uniform. Then, spray gold on the polyurethane sheets for two minutes.
[0008] Step 3: Use an impedance meter (Agilent 4294A) to clamp the gold-sprayed part to measure the capacitance value of the material, and measure the dielectric constant of pure polyurethane without glass beads and the dielectric constant of the glass beads and polyurethane two-phase composite material;
[0009] Step 4: Calculate the dielectric constant of the two-phase composite material of polyurethane and glass microspheres:
[0010] According to the capacitance calculation formula:
[0011]
[0012] ε0 is the dielectric constant in vacuum:
[0013]
[0014] The calculation formula of dielectric constant can be obtained:
[0015]
[0016] Step 5: Calculate the dielectric constant of glass beads
[0017] The glass beads in the glass beads and polyurethane composites are considered to be evenly arranged in the polyurethane, that is, a polyurethane cube containing one glass bead is the basic unit of the composite material. The volume of this basic unit can be calculated according to the volume fraction of the glass beads. Because the diameter and arrangement of the glass beads are somewhat different in practice, the electric flux density D of the composite material can be calculated using the weighted square method.
[0018] The calculation formula is:
[0019] {D}={ε0ε r {E}
[0020] ε r is the dielectric constant of glass beads / polyurethane;
[0021] If the material is anisotropic, the formula can be written as:
[0022]
[0023] According to the mean field theory, assuming that the polyurethane matrix containing glass microspheres is isotropic, the formula can be written as:
[0024] D=ε0ε r E
[0025] The electric flux density of glass microsphere / polyurethane in the smallest unit can be obtained by adding the electric flux densities of polyurethane and glass microsphere; that is,
[0026] D0=D1+D2
[0027]
[0028] D0: Electric flux density of glass beads / polyurethane
[0029] D1: Electrical flux density of pure polyurethane
[0030] D2: Electric flux density of glass beads
[0031] ε r1 : Dielectric constant of pure polyurethane
[0032] ε r2 : Dielectric constant of glass microspheres
[0033] The dielectric constant of the glass microspheres can be obtained by measuring the dielectric constants of the pure polyurethane matrix and the glass microspheres / polyurethane matrix.
[0034] Furthermore, in the step 1, preparing the polyurethane solid uniformly mixed with glass microbeads comprises the following steps:
[0035] 1) Molecular sieves are placed in the combined polyether and placed in a drying oven at 50°C for 10 hours. This step is to remove water molecules in the combined polyether to avoid bubbles when isocyanate is subsequently reacted with the combined polyether, which makes it impossible to obtain the dielectric constant of the pure polyurethane matrix.
[0036] 2) Put the isocyanate in a drying oven at 70°C for half an hour. This step is because the isocyanate liquid is relatively thick at room temperature. After heating, the isocyanate liquid has enhanced fluidity, which is convenient for subsequent liquid weighing. It can also dry the hydrocyanate and its container, and the vacuum agitator is used to ensure its dryness.
[0037] 3) First, weigh the combined polyether and place it in a vacuum stirrer container, then weigh the glass beads and add them to the combined polyether, and use the vacuum stirrer to mix them evenly without generating bubbles; finally, weigh the isocyanate and add it to the mixture of the combined polyether and the glass beads, and use the vacuum stirrer to vacuum the final mixture again and stir for 8-10 minutes;
[0038] 4) The stirred polyurethane is placed in an environment of about 60° C. to allow it to react quickly to obtain pure polyurethane solid.
[0039] After adopting the above structure, the beneficial effects of the present invention are as follows: the present invention proposes a method for measuring the dielectric constant of glass microspheres, by preparing a composite of polyurethane and glass microspheres, measuring the dielectric constant of the composite and the dielectric constant of polyurethane without glass microspheres, and finally obtaining the dielectric constant of the glass microspheres. The actual measured dielectric constant is very close to the data obtained under the average field, and the lower the dielectric constant of the material itself, the closer the data. In this way, the dielectric constant of the glass microspheres can be obtained when the dielectric constants of the pure polyurethane matrix and the glass microsphere / polyurethane matrix are measured. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0042] Embodiment 1:
[0043] Prepare a polyurethane matrix without glass microspheres:
[0044] (1) placing molecular sieves in the composite polyether and placing it in a drying oven at 50° C. for reaction for 10 hours;
[0045] (2) Place the isocyanate in a drying oven at 70°C for half an hour;
[0046] (3) First, 12.24 g of the combined polyether was weighed and placed into a vacuum stirrer container, and then 9.79 g of isocyanate was weighed and added to the combined polyether. The final mixture was again vacuumed and stirred for 8-10 minutes using the vacuum stirrer;
[0047] (4) The stirred polyurethane is placed in an environment of about 60° C. to allow it to react quickly to obtain pure polyurethane solid.
[0048] Example 2: Preparation of a polyurethane matrix with a glass microsphere mass fraction of 6%
[0049] (1) placing molecular sieves in the composite polyether and placing it in a drying oven at 50° C. for reaction for 10 hours;
[0050] (2) Place the isocyanate in a drying oven at 70°C for half an hour;
[0051] (3) First, 11.28 g of the combined polyether was weighed and placed in a vacuum stirrer container, then 1.32 g of glass microspheres were weighed and added to the combined polyether and mixed evenly using a vacuum stirrer without generating bubbles, and finally 9.4 g of isocyanate was weighed and added to the mixture of the combined polyether and the glass microspheres, and the final mixture was again vacuumed and stirred using a vacuum stirrer for 8-10 minutes;
[0052] (4) The stirred polyurethane is placed in an environment of about 60° C. to allow it to react quickly to obtain a polyurethane solid uniformly mixed with glass microbeads.
[0053] Example 3: Preparation of a polyurethane matrix with a glass microsphere mass fraction of 12%
[0054] (1) placing molecular sieves in the composite polyether and placing it in a drying oven at 50° C. for reaction for 10 hours;
[0055] (2) Place the isocyanate in a drying oven at 70°C for half an hour;
[0056] (3) First, 10.75 g of the combined polyether was weighed and placed in a vacuum stirrer container, then 2.64 g of glass microspheres were weighed and added to the combined polyether and mixed evenly using a vacuum stirrer without generating bubbles, and finally 8.60 g of isocyanate was weighed and added to the mixture of the combined polyether and the glass microspheres, and the final mixture was vacuumed and stirred again using a vacuum stirrer for 8-10 minutes;
[0057] (4) The stirred polyurethane is placed in an environment of about 60° C. to allow it to react quickly to obtain a polyurethane solid uniformly mixed with glass microbeads.
[0058] Example 4: Preparation of a polyurethane matrix with a glass microsphere mass fraction of 15%
[0059] (1) placing molecular sieves in the composite polyether and placing it in a drying oven at 50° C. for reaction for 10 hours;
[0060] (2) Place the isocyanate in a drying oven at 70°C for half an hour;
[0061] (3) First, 10.38 g of the combined polyether was weighed and placed in a vacuum stirrer container, then 3.3 g of glass microspheres were weighed and added to the combined polyether and mixed evenly using a vacuum stirrer without generating bubbles, and finally 8.3 g of isocyanate was weighed and added to the mixture of the combined polyether and the glass microspheres, and the final mixture was vacuumed and stirred again using a vacuum stirrer for 8-10 minutes;
[0062] (4) The stirred polyurethane is placed in an environment of about 60° C. to allow it to react quickly to obtain a polyurethane solid uniformly mixed with glass microbeads.
[0063] The products prepared in the above Examples 1-4 were polished into square sheets with a diameter of 1 cm and a thickness of 0.5-1 mm. The thickness of the sheets was required to be uniform. The polyurethane sheets were then sprayed with gold for two minutes. The capacitance of the material was measured by clamping the gold-sprayed part with an impedance meter (Agilent 4294A).
[0064] Calculate the dielectric constant of a two-phase composite of polyurethane and glass microspheres:
[0065] According to the capacitance calculation formula:
[0066]
[0067] ε0 is the dielectric constant in vacuum:
[0068]
[0069] The calculation formula of dielectric constant can be obtained:
[0070]
[0071] Calculating the dielectric constant of glass microspheres
[0072] The glass beads in the glass beads and polyurethane composite material are regarded as uniformly arranged in the polyurethane, that is, the polyurethane cube containing one glass bead is the basic unit of the composite material. The volume of this basic unit can be calculated according to the volume fraction of the glass beads. Because the diameter and arrangement of the glass beads are somewhat different in practice, the weighted square method can be used to calculate the electric flux density D of the composite material.
[0073] The calculation formula is:
[0074] {D}={ε0ε r {E}
[0075] ε r is the dielectric constant of glass beads / polyurethane;
[0076] If the material is anisotropic, the formula can be written as:
[0077]
[0078] According to the mean field theory, assuming that the polyurethane matrix containing glass microspheres is isotropic, the formula can be written as:
[0079] D=ε0ε r E
[0080] In the smallest unit, the electric flux density of glass microsphere / polyurethane can be obtained by adding the electric flux density of polyurethane and glass microsphere.
[0081] D0=D1+D2
[0082]
[0083] D0: Electric flux density of glass beads / polyurethane
[0084] D1: Electrical flux density of pure polyurethane
[0085] D2: Electric flux density of glass beads
[0086] ε r1 : Dielectric constant of pure polyurethane
[0087] ε r2 : Dielectric constant of glass microspheres
[0088] The actual measured dielectric constant is very close to the data obtained under the average field, and the lower the dielectric constant of the material itself, the closer the data. In this way, the dielectric constant of the glass microspheres can be obtained by measuring the dielectric constants of the pure polyurethane matrix and the glass microspheres / polyurethane matrix.
[0089] Although the embodiments of the present invention have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents. In short, if those skilled in the art are inspired by them and design structural modes and embodiments similar to the technical solution without creativity without departing from the purpose of the present invention, they shall all fall within the scope of protection of the present invention.
Claims
1. A method for measuring the dielectric constant of glass microspheres, comprising the following steps: Step 1: preparing a polyurethane solid uniformly mixed with glass microspheres, and preparing a polyurethane matrix without glass microspheres and three groups of polyurethane matrices with different glass microsphere mass fractions; Step 2: Grind the polyurethane substrates obtained in step 1 into square sheets with a diameter of 1 cm and a thickness of 0.5-1 mm, and the thickness of the sheets is required to be uniform. Then, spray gold on the polyurethane sheets for two minutes. Step 3: Use an impedance meter (Agilent 4294A) to clamp the gold-sprayed part to measure the capacitance value of the material, and measure the dielectric constant of pure polyurethane without glass beads and the dielectric constant of the glass beads and polyurethane two-phase composite material; Step 4: Calculate the dielectric constant of the two-phase composite material of polyurethane and glass microspheres: According to the capacitance calculation formula: ε0 is the dielectric constant in vacuum: The calculation formula of dielectric constant can be obtained: Step 5: Calculate the dielectric constant of glass beads The glass beads in the glass beads and polyurethane composites are considered to be evenly arranged in the polyurethane, that is, a polyurethane cube containing one glass bead is the basic unit of the composite material. The volume of this basic unit can be calculated based on the volume fraction of the glass beads. Because the diameter and arrangement of the glass beads are somewhat different in practice, the electric flux density D of the composite material is calculated using the weighted square method; The calculation formula is: {D}={ε0ε r {E} ε r is the dielectric constant of glass beads / polyurethane; If the material is anisotropic, the formula can be written as: According to the mean field theory, assuming that the polyurethane matrix containing glass microspheres is isotropic, the formula can be written as: D=ε0ε r E In the smallest unit, the electric flux density of glass microsphere / polyurethane can be obtained by adding the electric flux density of polyurethane and glass microsphere, that is, D0: Electric flux density of glass beads / polyurethane D1: Electrical flux density of pure polyurethane D2: Electric flux density of glass beads ε r1 : Dielectric constant of pure polyurethane ε r2 : Dielectric constant of glass microspheres The dielectric constant of the glass microspheres can be obtained by measuring the dielectric constants of the pure polyurethane matrix and the glass microspheres / polyurethane matrix.
2. The method for measuring the dielectric constant of glass microspheres according to claim 1, characterized in that: In the step 1, preparing a polyurethane solid uniformly mixed with glass microspheres comprises the following steps: 1) placing a molecular sieve in the composite polyether and placing it in a drying oven at 50° C. for 10 hours to remove water molecules in the composite polyether; 2) Place the isocyanate in a drying oven at 70°C for half an hour to heat it for subsequent liquid weighing; 3) First, weigh the combined polyether and place it in a vacuum stirrer container, then weigh the glass beads and add them to the combined polyether, and use the vacuum stirrer to mix them evenly without generating bubbles; finally, weigh the isocyanate and add it to the mixture of the combined polyether and the glass beads, and use the vacuum stirrer to vacuum the final mixture again and stir for 8-10 minutes; 4) The stirred polyurethane is placed in an environment of about 60° C. to allow it to react quickly to obtain pure polyurethane solid.
Citation Information
Patent Citations
Radar wave absorbing paint with hollow microsphere as filling material and preparation method thereof
CN101294047A
Epoxide resin pouring sealant with low density and high impact resistance and preparation method thereof
CN101580686A